EXPRESSION OF SYNONYMIC RELATIONSHIPS IN TONGUE TWISTERS WITH THE CONCEPT PLANT - Isakova Elvina Dilaverovna (Web of Journals Publishing, 2026)
This article explores the expression of synonymic relationships in tongue twisters containing the conceptual domain plant. Tongue twisters, as a special type of paremiological unit, combine phonetic complexity with semantic density. The study focuses on how plant-related lexemes enter into synonymic relations, contributing to expressiveness, memorability, and linguistic play. Examples from English (with comparative references to other languages where relevant) illustrate how synonymy operates at lexical, contextual, and stylistic levels.
Keywords: Tongue twister, synonymy, plant concept, paremiology, lexical semantics, stylistics.